Clinical practice guideline on atraumatic (pencil‐point) vs conventional needles for lumbar puncture: Endorsement by the Scandinavian Society of Anaesthesiology and Intensive Care Medicine. Issue 4 (17th January 2019) - Rehn, Marius; Chew, Michelle S.; Olkkola, Klaus T.; Sverrison, Kristinn Ö.; Yli‐Hankala, Arvi; Møller, Morten Hylander
Abstract : The Scandinavian Society of Anaesthesiology and Intensive Care Medicine Clinical Practice Committee endorses the BMJ Rapid Recommendation clinical practice guideline on atraumatic (pencil‐point) vs conventional needles for lumbar puncture. This includes the strong recommendation for the use of atraumatic needles for lumbar puncture in all patients regardless of age or indication.